Further exploration of C++ templates and metaprogramming learn advanced techniques, including features introduced in C++ 11 and C++ 14, that ease working with templates and produce extremely efficient code - Templeman, Julian (O'Reilly, 2017)
"Designed for intermediate level C++ programmers, this course focuses on the advanced features and techniques made possible by the release of C++11 and C++14. It introduces several new Standard Library types, and investigates type aliases and static assertions, two features that make it easy to work with templates. You will also explore variadic templates, which allow developers to write type-safe functions and classes that take variable numbers and types of arguments. The course wraps up by examining template metaprogramming, an expert technique that generates code at compile time, produces extremely efficient code with no run-time overhead, and is widely used in modern C++ libraries."--Resource description page.
Title from title screen (viewed June 20, 2017). - Date of publication from resource description page
Keywords: C++ (Computer program language); Object-oriented programming languages; C++ (Langage de programmation); Langages orientés objet (Informatique)